2017
DOI: 10.21093/ijeltal.v1i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Reading in Developing Language Competency for Indonesian EFL Learners Majoring in English

Abstract: Abstract:Extensive reading might develop EFL learners ' English competency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
(12 reference statements)
2
19
0
Order By: Relevance
“…Meanwhile, for making college learners have a lot of experience on comprehending a text, vocabulary, and grammar or structure, the Lecturers can give them a task. It is in line with Martini (2008) in Delfi and Yamat (2017) whereas she gives suggestions toward the teacher or lecturer for giving motivation to students to read a lot of reading material, be creative in finding interesting reading material, be a good model, giving a lot of reading tasks which can be read at home, and control the students' reading activities outside of the classroom by using written report.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Meanwhile, for making college learners have a lot of experience on comprehending a text, vocabulary, and grammar or structure, the Lecturers can give them a task. It is in line with Martini (2008) in Delfi and Yamat (2017) whereas she gives suggestions toward the teacher or lecturer for giving motivation to students to read a lot of reading material, be creative in finding interesting reading material, be a good model, giving a lot of reading tasks which can be read at home, and control the students' reading activities outside of the classroom by using written report.…”
Section: Discussionsupporting
confidence: 61%
“…Reading itself is the process of receiving and interpreting information encoded in language form via the medium of print, Grabe (2009:14). Besides that, reading English texts has importants roles for EFL learners majoring in English since reading is not only as a subject but also as an activity done in studying other English course, Delfi & Yamat (2017). In fact, learning reading is not learning how to read a text only, but also learning about vocabulary, and grammar.…”
Section: Introductionmentioning
confidence: 99%
“…Different from intensive reading, which focuses on gaining the deep meaning of the text, extensive reading is known as reading for enjoyment in which the readers read a lot of easy texts in the new language and independently read for general understanding and overall meaning. In these activities, students can choose books according to their abilities of language and minimize the use of a dictionary on those activities (Delfi & Yamat, 2017). Boakye (Boakye, 2017) claims that extensive reading, along with the other kinds of reading, is conducted to help students increase their reading skills and develop their cognitive and affective abilities.…”
Section: Extensive Reading In Efl Classroommentioning
confidence: 99%
“…The writers' experiences in implementing extensive reading is broadly in line with Ho-Hyak Jang et al (2015) who found that the affect of extensive reading activities have a positive influence on students' reading proficiency and their intrinsic motivation Korea. The result of a study conducted by Delfi & Yamat (2017) shows the current context of Indonesian reading performances. Learners increase reading competency through extensive reading (Milliners, 2017).…”
Section: Introductionmentioning
confidence: 99%